Did the increase in the results of competitive swimming cease after banning the use of new technology swimming suits? - Zuoziene, I. J. (Acta Kinesiologiae Universitatis Tartuensis, 2011)
Swimming is one of few branches of sport where new technologies in sportswear did not have any serious impact in the history of its development. However, at the beginning of the 21st century SPEED Company cooperating with Australian Sports Institute started looking for novelties producing LZR Racer swimming suits applying high technology materials from nylon, elastic and polyurethane. Advertising new swimming suits producers claimed that the suits facilitated the easier process of oxygen getting into muscles, the body was held in a more effective position from a hydrodynamic standpoint, water was repelled, and the seams were fastened by ultrasound for lower water resistance. It was suggested that the speed of swimmers in those suits increased by 1.9-2.2 per cent. In Beijing Olympic Games 94% of swimmers wore LZR Racer, 23 out of 25 world records were beaten wearing those suits. After the Olympic Games, such producers as Jaked, Arena X-Glide, Adidas Hydrofoil, Descente Aquaforce suggested making new technology "super swimming suits". The process of beating world records became faster. However, the International Swimming Federation opposed to "technological doping", and since 2010 the new swimming suits were forbidden because in swimming the results must depend only on athlete`s physical fitness. Thus, in our study we aimed at answering the following research question: did the increase of results in competitive swimming cease after new technology swimming suits had been forbidden? Research aim was to analyze the dynamics of contest indices of elite male swimmers in the period of 2000-2010. Methods. On the basis of R. Haljand`s methods (www.swim.ee) we analyzed the dynamics of results and contest indices in 100 m freestyle and 100 m breaststroke in the world championships of 2000, 2002, 2004, 2006, 2008 and 2010. The sample consisted of swimmers who participated in the finals the chosen events (n=8), i.e. the research materials included 96 cases. We analyzed the contest protocols, and the following standard indices were estimated: swimming speed at the start, turn, finish, stable locomotion, swimming pace and the length of a stroke. Results: The mean index of swimming results in the finals from 2000 till 2010 improved statistically significantly in 100 m freestyle (t=3.80, p<0.01) and 100 m breaststroke (t=6.65, p<0.01) distances, but from 2008 till 2010 no significant difference was observed (p>0.05). Until 2008, in 100 m freestyle distance, the fast increase in swimming speed was noticed only at turns, the last quarter and at the finish. Those tendencies were noticeable also in the championship of 2010. Male swimmers in 100 m breaststroke im roved their start, turn and finish techniques and significantly increased their swimming speed (t=4.70-9.29, p<0.001), their stroke length and average swimming speed increased as well (t=2.17-2.54, p<0.05). In the world championship of 2010, statistically significantly higher speed was observed in the start and finish distances. The analysis of the research results showed that covering 100 m distance in different styles the swimming pace and the length of stroke did not change. Conclusions: 1. The increase in results of European elite swimmers in 100 m freestyle and breaststroke was mostly influenced (p<0.001) by swimming speed at the star, turn and finish, and those tendencies were observed during the whole period in question. 2. Research results in 2008-2010 did not change significantly (p>0.05), but we could observe tendencies in the increase of swimming speed in the final part of the swimming distance.